Bio-based polyurethane as well as preparation method and application thereof
Bio-based polyurethane is prepared by using isophorone diisocyanate and castor oil and combined with corn protein to prepare biodegradable corn protein/bio-based polyurethane nanofiber membranes, solving the problem of non-renewable and non-degradable petroleum-based plastic packaging materials, achieving high-performance and environmentally friendly packaging materials.
Patent Information
- Application Number
- CN202411731324.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-25
AI Technical Summary
The existing petroleum-based plastic packaging materials are non-renewable and non-degradable, resulting in environmental pollution and resource depletion, and the mechanical properties of the zein nanofiber membrane are poor, limiting its application.
Bio-based polyurethane is prepared by isophorone diisocyanate and castor oil, and combined with zein through electrospin technology to prepare biodegradable zein/bio-based polyurethane nanofiber membranes.
By reasonably adjusting the rheological characteristics of the solution, controlling the morphological characteristics of the nanofiber membrane, improving its tensile strength and elongation of breakage, and the weight loss rate of the material is 66% after 100 days, which is less polluted to the environment.
Smart Images

Figure CN119684553A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polyurethane materials, and in particular to bio-based polyurethane and a preparation method and application thereof. Background Art
[0002] Commonly used packaging materials include paper, petroleum-based plastics, metals, glass, ceramics, etc. Among them, petroleum-based plastics are the most widely used packaging materials due to their rigidity, flexibility, satisfactory barrier properties, low cost and easy processing. However, due to the non-renewable and non-degradable nature of petroleum-based plastics, their extensive use has brought about serious environmental problems, including natural resource depletion, garbage pollution and global warming. Therefore, there is an urgent need to develop bio-based polymers to reduce the widespread use of petroleum-based plastics.
[0003] Zein is a derivative product of corn processing enterprises. It has been widely used in food packaging and preservation due to its special properties such as high heat resistance, excellent antioxidant and hydrophobicity, such as QIN Q, WEID, GAN J, et al. Preparation of environmental-benign castor oil-derived polyurethane thermal conductive structural adhesives with superior strength [J]. Polymer, 2024. Although pure zein nanofiber membranes have been prepared in previous studies, the mechanical properties of these nanofiber membranes are poor, such as CHAI W, ZHANG L, LI W, et al. Preparation of Plastics-and Foaming Agent-Free and Porous Bamboo Charcoal based Composites Using Sodium Silicate as Adhesives [J]. Materials, 2021. This greatly limits the application of zein.
[0004] Therefore, the present inventors studied the preparation of bio-based polyurethane using isophorone diisocyanate and castor oil, and applied the bio-based polyurethane to prepare biodegradable zein / bio-based polyurethane nanofiber membranes by electrospinning technology. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention aims to provide a bio-based polyurethane and a preparation method and application thereof.
[0006] In order to achieve the first purpose, the present invention provides the following technical solutions:
[0007] Bio-based polyurethane uses castor oil as polyol of polyurethane, isophorone diisocyanate as polyisocyanate of polyurethane, and 1,4-butanediol as chain extender of polyurethane to prepare bio-based polyurethane solution.
[0008] In order to achieve the second purpose, the present invention provides the following technical solutions:
[0009] The preparation method of bio-based polyurethane comprises the following steps: putting isophorone diisocyanate, acetone and 1,4-butanediol into a dry round-bottom flask, adding castor oil within 10 minutes after reacting for 2 hours, and continuing the reaction for another 2 hours to obtain a high-viscosity mixture; then adding a solvent, removing the acetone by rotary evaporation, and obtaining a bio-based polyurethane solution.
[0010] Preferably, the castor oil is vacuum dried at 120° C. for 2 h; the 1,4-butanediol is vacuum dried at 60° C. for 3 h, and the solvent is N,N-dimethylformamide.
[0011] Preferably, the reaction temperature is 60°C.
[0012] In order to achieve the third purpose, the present invention provides the following technical solutions:
[0013] Application of bio-based polyurethane for the preparation of zein / bio-based polyurethane nanofiber membranes.
[0014] The method for preparing the zein / bio-based polyurethane nanofiber membrane comprises the following steps:
[0015] S1: dissolving zein in a solvent to prepare a zein solution, adding the bio-based polyurethane solution to the zein solution, and stirring at room temperature for 12 hours to obtain a uniform bio-based polyurethane spinning solution;
[0016] S2: The spinning solution is sucked up with a syringe and fixed on the propulsion pump, the needle is pulled and fixed on the reciprocating platform and connected to a DC high-voltage power supply, and the tin foil is wrapped on a metal roller receiving device as a collection device for the nanofiber membrane to obtain the corn protein / bio-based polyurethane nanofiber membrane.
[0017] Preferably, the mixing ratio of the corn protein solution to the bio-based polyurethane solution is 1.5-3.5:4.
[0018] Preferably, the mixing ratio of the corn protein solution to the bio-based polyurethane solution is 3:4.
[0019] Preferably, the solvent in step S1 is N,N-dimethylformamide.
[0020] Preferably, in step S2, the propulsion flow rate of the propulsion pump is 0.5 mL / min, and the positive high voltage of the DC high voltage power supply is 0 to 30 kV.
[0021] The present invention has significant technical effects due to the adoption of the above technical solution:
[0022] The present invention uses isophorone diisocyanate and castor oil to prepare bio-based polyurethane, and the bio-based polyurethane is combined with corn protein to prepare a biodegradable corn protein / bio-based polyurethane nanofiber membrane. Specific experimental studies have shown that the morphological characteristics of the nanofiber membrane can be effectively controlled by rationally adjusting the rheological properties of the solution. When the mass of corn protein is 4 grams, the mass of bio-based polyurethane is 3 grams, and the mass of solvent DMF is 10 grams, the tensile strength (4.41±0.24MPa) of the nanofiber membrane is the maximum, and the elongation at break (7.68±0.32%) is the maximum. The corn protein and castor oil used to prepare the bio-based polyurethane come from nature, can be degraded, and the weight loss rate after 100 days is 66%, which has less pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Diagram of the synthesis steps of bio-based polyurethane.
[0024] Figure 2 SEM images of different nanofiber membranes at 15KV.
[0025] Figure 3 SEM images of the nanofiber membrane (ZBPU3) under different voltages.
[0026] Figure 4 FTIR-ATR and XRD patterns of zein / bio-based polyurethane nanofiber membrane.
[0027] Figure 5 This is the water contact angle diagram of zein / bio-based polyurethane nanofiber membrane.
[0028] Figure 6 The TGA curve of zein / bio-based polyurethane nanofiber membrane and its derivative curve.
[0029] Figure 7 Bar graph of tensile strength and elongation at break of zein / bio-based polyurethane nanofiber membrane.
[0030] Figure 8 Porosity diagram of zein / bio-based polyurethane nanofiber membrane.
[0031] Fig. 9 This is a graph showing the relationship between the weight loss rate of zein / bio-based polyurethane nanofibers and time. DETAILED DESCRIPTION
[0032] Example 1: Bio-based polyurethane, castor oil is used as the polyol of polyurethane, isophorone diisocyanate is used as the polyisocyanate of polyurethane, and 1,4-butanediol is used as the chain extender of polyurethane to prepare a bio-based polyurethane solution.
[0033] The above reagents are all commercially available products, specifically isophorone diisocyanate (IPDI), castor oil (CO), 1,4-butanediol (BDO) and N,N-dimethylformamide (DMF) purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and acetone purchased from Huzhou Shuanglin Chemical Technology Co., Ltd. The castor oil was vacuum dried at 120°C for 2h; the 1,4-butanediol was vacuum dried at 60°C for 3h.
[0034] Example 2: A method for preparing bio-based polyurethane, comprising the following steps: isophorone diisocyanate IPDI (7.14 g), acetone (5 ml) and 1,4-butanediol BDO (1.42 g) are placed in a dry round-bottom flask and reacted at 60°C for 2 hours. Then, 10 g of castor oil CO (R=1.01) is added within 10 minutes, and the reaction is continued for another 2 hours to obtain a high-viscosity mixture; then, 50 g of N,N-dimethylformamide DMF solvent is added, and acetone is removed by a rotary evaporator at 60°C to obtain a bio-based polyurethane solution. The synthesis steps are as follows: Figure 1 shown.
[0035] The bio-based polyurethane solution was poured into a glass dish, the solvent was removed in a vacuum oven at 60 °C, and the resulting polyurethane film was peeled off from the glass surface for further characterization.
[0036] Example 3: Application of bio-based polyurethane for preparing zein / bio-based polyurethane nanofiber membrane.
[0037] The method for preparing the zein / bio-based polyurethane nanofiber membrane comprises the following steps:
[0038] S1: 4 g of zein was dissolved in 10 ml of DMF to prepare a zein solution, followed by the addition of the bio-based polyurethane solution and stirring at room temperature for 12 h to obtain a uniform mixture. According to the mass ratio of bio-based polyurethane to zein in the solution composition (1.5:4, 2:4, 3:4, 3:4, 3.5:4), the samples were named ZBPU1.5, ZBPU2, ZBPU2.5, ZBPU3, and ZBPU3.5. The pure zein control group was marked as ZEIN. Before electrospinning, the viscosity of the solution was measured at 25 °C using a stress-controlled rheometer.
[0039] S2: Use a 5mL syringe to absorb a certain amount of spinning solution, fix it on the propulsion pump, set the propulsion flow rate to 0.5mL / min, pull the needle to the reciprocating platform and connect it to a DC high-voltage power supply (positive high voltage 0-30kV), and wrap the tin foil on the metal roller receiving device as a collection device for the nanofiber membrane.
[0040] The following specific experiments are used for testing and characterization:
[0041] 1. Test and characterization of corn protein / bio-based polyurethane nanofiber membrane structure:
[0042] (1) The morphology of bio-based polyurethane fiber membrane was studied using SEM;
[0043] SEM images of different nanofiber membranes at 15KV are shown in Figure 2. Figure 2 As shown, Figure 2 (a) ZEIN, (b) ZBPU1.5, (c) ZBPU2, (d) ZBPU2.5, (e) ZBPU3; SEM images of nanofiber membrane (ZBPU3) under different voltages Figure 3 As shown, Figure 3 (a) 13KV, (b) 15KV, (c) 17KV. At the same time, the performance and fiber diameter of the samples were tested, as shown in Table 1.
[0044] Table 1 Properties and fiber diameters of samples
[0045]
[0046] Table 1 summarizes the composition, viscosity, and average nanofiber diameter (AFD) of zein and zein / bio-based polyurethane solutions. Figure 2 The morphology of zein / biobased polyurethane nanofibers prepared by electrospinning is shown. The solution viscosity has a great influence on the morphology of the nanofibrous membrane, and changes in polymer concentration will also cause changes in solution viscosity. Therefore, we studied the relationship between solution viscosity and biobased polyurethane content. The solution viscosity increased with the increase in biobased polyurethane content. This may be due to the exponential increase in the internal friction resistance of the spinning solution and the decrease in molecular mobility. With the increase in biobased polyurethane concentration, the viscosity of the solution increased steadily, and the diameter of the nanofibrous membrane also increased steadily from 170±10nm to 360±20nm. No microbeads appeared in these nanofibrous membranes. When the weight of biobased polyurethane increased to 3.5g (ZPU3.5), the solution could not be electrospun into nanofibers. This is because the ZBPU3.5 solution was particularly turbid before electrospinning, indicating that zein aggregates were already present in the solution, and these zein aggregates may not be stretched along the nanofibrous matrix during the electrospinning process. Voltage is also an important parameter affecting the electrospinning process. Figure 3Scanning electron micrographs of zein / bio-based polyurethane nanofiber membranes at different voltages are shown. It can be seen from the figure that at low voltages (13kV, 15kV), the diameter of the electrospun nanofiber membrane is relatively uniform, no beads appear, and the fiber diameter at 15kV (360±20nm) is smaller than the fiber diameter at 13kV (390±15nm). When the voltage is increased to 17kV, microbeads appear in the electrospun fibers due to the instability of the jet. Under the action of the electric field force, the polymer solution or melt overcomes the surface tension, produces a jet, and finally solidifies to form electrospun polymer nanofibers. Increasing the voltage means increasing the charge density and jet velocity. Therefore, at low voltages, increasing the voltage is beneficial to reducing the diameter of the nanofibers. When the voltage is high, the jet is not easy to stabilize, so microbeads are more likely to appear. When the voltage is further increased, the instability of the jet increases, resulting in the appearance of microbeads in the nanofibers. In order to obtain higher porosity, we hope to obtain nanofibers with smaller diameters without the appearance of beads, so as not to affect the mechanical properties of the nanofiber membrane. Therefore, the voltage was controlled at 15KV in the subsequent experiments.
[0047] (2) Characterization of PLA fiber structure and functional groups by FT-IR;
[0048] Figure 4 (a) shows the FTIR-ATR spectra of zein / biobased polyurethane nanofiber membrane, pure zein nanofiber membrane and biobased polyurethane film. In biobased polyurethane, the C=O stretching band of the polyurethane bond appears at 1701 cm -1 , while the NH stretching zone and bending zone appear at 3323 cm -1 and 1525cm -1 In addition, 2260cm -1 The -NCO stretching band at 3300 cm-1 disappeared, indicating that the isocyanate groups were completely consumed, which can indicate that the blocked polyurethane was successfully prepared. -1 、1650cm -1 and 1543cm -1 .3300cm -1 The characteristic peak at 1650 cm-1 can be attributed to the presence of amide A (NH bond and OH bond) of amino acids, while the peak at 1650 cm-1 can be attributed to the presence of amide A (NH bond and OH bond) of amino acids. -1 and 1543cm -1 The peaks at indicate the presence of amide I (C=O stretching) and amide II (NH bending band and CN stretching band), respectively. Figure 4 As can be seen in (a), the spectrum of zein / biobased polyurethane nanofibers shows common bands of biobased polyurethane and zein, which indicates that biobased polyurethane is successfully introduced into zein nanofibers.-1 -2960cm -1 The bands are gradually enlarged in the following order: ZBPU1.5 <ZBPU2<ZBPU2.5<ZBPU3。
[0049] (3) Use XRD to analyze the surface composition of the film; use a contact angle tester to characterize the water contact angle of the sample;
[0050] Bio-based polyurethane films, zein, and zein / bio-based polyurethane nanofiber membranes were studied by XRD to further determine the physical structure and distribution of bio-based polyurethane in zein nanofiber membranes. The XRD images of pure zein / bio-based polyurethane nanofiber membranes and zein / bio-based polyurethane nanofiber membranes are shown in Figure 2. Figure 4 (c) shows that the bio-based polyurethane exhibits a broad peak at 2θ=20°, which is due to the fact that it is an amorphous polymer. The zein nanofiber membrane exhibits a broad peak at 2θ=22.5°, which originates from the crystalline structure of the α-helix. However, the crystallinity of the zein nanofiber membrane is very low, which may be due to the destruction of its ordered structure in the solvent DMF. The zein / bio-based polyurethane nanofiber membrane also has the same characteristic peaks as the bio-based polyurethane, which proves that the addition of zein does not change the properties of the bio-based polyurethane.
[0051] (4) Characterizing the water contact angle of the sample using a contact angle meter;
[0052] The hydrophilicity of zein / bio-based polyurethane nanofiber membranes and bio-based polyurethane films was evaluated by measuring water contact angles. Figure 5 As shown, Figure 5 (a) Figure 5 (b) Figure 5 (c) Figure 5 (d) Figure 5 (e) Figure 5 (f) Corresponds to BPU, ZBPU1.5, ZBPU2, ZBPU2.5, ZBPU3, ZEIN, respectively. Hydrophobicity or water resistance is crucial for many potential uses such as biomaterials, liquid filters, and layered composites. The results showed that the zein / biobased polyurethane nanofiber membrane is hydrophobic, with a water contact angle between 76° and 90°, slightly larger than that of the biobased polyurethane film (75°).
[0053] (5) Perform thermogravimetric characterization of the sample using a thermogravimetric analyzer under a N2 atmosphere;
[0054] Table 2 Properties and fiber diameters of samples
[0055]
[0056] Figure 6 The thermogravimetric curve (a) and its derivative curve (b) of the sample are shown. Table 2 summarizes the TGA data of the nanofiber membrane, as well as the temperatures corresponding to 10% weight loss (T10), 50% weight loss (T50) and residue at 600°C. The pure zein nanofiber membrane has a weight loss (about 3.5%) at 100°C due to the evaporation of trace water in the sample. A slight weight loss was also observed between 125°C and 200°C. This weight loss may be caused by the residual solvent (DMF) in the nanofibers. The main weight loss of zein nanofibers occurs at 265-350°C, which is consistent with the basic degradation temperature of electrospun zein nanofibers. The degradation of bio-based polyurethane film includes three degradation processes. Initially, the weight loss of the film in the temperature range of 200-320°C is due to the decomposition of the hard segment formed by the polyurethane group and urea bond in the polymer chain, thereby forming primary amines, isocyanates, olefins, etc. The second stage decomposes in the temperature range of 320-400°C, and the weight loss process is the fastest, due to the cleavage of castor oil fatty acid chains. The decomposition above 400 °C is related to the further thermal oxidation of the bio-based polyurethane film. Two degradation steps were found in the TGA curves of zein / bio-based polyurethane nanofibers. The weight loss of each sample was slightly different. For ZBPU3, the first stage was from 135 °C to 370 °C, and the second stage was from 370 °C to 600 °C. As the mass of bio-based polyurethane in zein / bio-based polyurethane nanofibers increased, the residual amount at 600 °C also decreased. In the temperature range of 450-600 °C, the stability of the nanofibers decreased with the increase of bio-based polyurethane content. Moreover, it is worth noting that the actual weight percentage is greater than the theoretical mass percentage. The possible reason is that the hydrogen bonds formed between zein and bio-based polyurethane are beneficial to improve the thermal stability of the blended film.
[0057] (5) The mechanical properties of bio-based polyurethane fiber membrane were measured using a tensile strength testing machine.
[0058] Figure 7 A bar graph of tensile strength and elongation at break of zein / bio-based polyurethane nanofiber membranes is shown. The tensile strength of pure zein nanofiber membrane is 1.55±0.16MPa, and the elongation at break is 5.29±0.69%. Compared with pure zein nanofiber membrane, zein nanofiber membrane with added bio-based polyurethane has greater tensile strength and elongation at break. The tensile strength and elongation at break increase with the increase of bio-based polyurethane content. It is worth noting that the tensile strength of ZBPU3 is 4.41±0.24MPa, and the elongation at break is 7.68±0.32%. Combined Figure 8It can be seen that the porosity of the membrane material is closely related to the breaking strength of the fiber. The larger the porosity, the smaller the breaking strength. This is mainly because the pore structure reduces the mutual constraint links between the fibers and reduces the flexibility, so the fiber membrane becomes easier to break. The above phenomenon can be attributed to two factors. On the one hand, the introduction of polymer chains with better mechanical properties significantly improves the mechanical properties of the composite membrane. On the other hand, the performance of hydrogen bonds and interpenetrating networks increases the cross-linking density and prevents the chains from sliding against each other. Therefore, the tensile strength and elongation at break of the composite membrane are better than the control strength of pure corn protein membrane. Aylim et al. prepared corn protein / tributyl citrate nanofiber membrane by mixed electrospinning technology. Compared with pure corn protein nanofiber membrane, the tensile strength (2.47±0.21MPa) of the nanofiber membrane doped with tributyl citrate increased, but the elongation at break did not change. Akrami et al. prepared corn protein / silk fibroin / chitosan nanofiber membrane by mixed electrospinning technology. The tensile strength of the prepared composite nanofiber membrane is 3.45MPa.
[0059] 2. Porosity test:
[0060] A 2 cm × 2 cm nanofiber membrane was cut from the nanofiber membrane and immersed in deionized water for 24 h. The membrane was taken out and the surface was wiped dry. The membrane was weighed and the thickness of the membrane was measured with a thickness meter. The membrane was then dried in an oven at 60 ° C to a constant weight and weighed again. The total porosity was determined by the weight method and calculated according to the following formula:
[0061]
[0062] Where ε is the porosity, %; Ww is the wet weight, g; Wd is the dry weight, g; A is the area of the nanofiber membrane, cm 2 ; L is the film thickness, cm; ρ is the density of water, 1g / cm 3 .
[0063] Figure 8 The porosity of pure zein and zein / biobased polyurethane nanofiber membranes is shown. The pure zein nanofiber membrane has the highest porosity (80 ± 1.41%). The porosity decreases with the increase of biobased polyurethane content. The difference in porosity is due to the hydrogen bonding between zein and biobased polyurethane molecules. When the weight of biobased polyurethane is 3g (ZBPU3), the number of hydrogen bonds between zein and biobased polyurethane molecules is the largest, the diameter of the nanofibers is the largest, the density is the highest, and therefore the porosity is the lowest.
[0064] 3. Biodegradation test:
[0065] Nanofiber samples (4 cm x 4 cm) were prepared and landfilled by burying the filter in soil to a depth of 5 cm. The soil on the filter sample block was carefully swept away and the weight was measured. The sample was then re-covered with soil. The weight loss was calculated as follows:
[0066]
[0067] Among them, m 0 and m1 represent the weight of the membrane before and after degradation, respectively.
[0068] The soil burial degradation method was used to verify the biodegradability of the nanofiber membrane. ZBPU3 nanofiber membrane was selected as the experimental sample because it has the best tensile strength and elongation at break. The weight loss rate of the nanofiber is shown in Fig. 9 As shown. After 100 days of degradation, the weight of the nanofiber membrane decreased by 66%. Zein is a derivative product of corn processing enterprises, mainly composed of protein, and also contains a small amount of starch and fiber, which can be completely degraded by microorganisms in the soil. The triglyceride structure in castor oil did not participate in the reaction and remained in the bio-based polyurethane. Microorganisms can gradually hydrolyze triglycerides into glycerol and fatty acids. The undegraded part of the nanofiber membrane may come from bio-based polyurethane. Therefore, the prepared zein / bio-based polyurethane nanofiber membrane has good biodegradability and little impact on the environment.
[0069] In summary, the present invention uses isophorone diisocyanate and castor oil to prepare bio-based polyurethane, and the bio-based polyurethane is combined with corn protein to prepare a biodegradable corn protein / bio-based polyurethane nanofiber membrane. Specific experimental studies have shown that the morphological characteristics of the nanofiber membrane can be effectively controlled by rationally adjusting the rheological properties of the solution. When the mass of corn protein is 4 grams, the mass of bio-based polyurethane is 3 grams, and the mass of solvent DMF is 10 grams, the tensile strength (4.41±0.24MPa) of the nanofiber membrane is the largest, and the elongation at break (7.68±0.32%) is the largest. The corn protein and castor oil used to prepare bio-based polyurethane come from nature and can be degraded. The weight loss rate after 100 days is 66%, and the pollution to the environment is relatively small.
Claims
1. Bio-based polyurethane, characterized in that The bio-based polyurethane solution is prepared by using castor oil as polyol of polyurethane, isophorone diisocyanate as polyisocyanate of polyurethane and 1,4-butanediol as chain extender of polyurethane.
2. The method for preparing bio-based polyurethane according to claim 1, characterized in that: The following steps are involved: Isophorone diisocyanate, acetone and 1,4-butanediol were placed in a dry round-bottom flask. After reacting for 2 hours, castor oil was added within 10 minutes and the reaction was continued for another 2 hours to obtain a high-viscosity mixture. Then, a solvent was added and the acetone was removed by rotary evaporation to obtain a bio-based polyurethane solution.
3. The method for preparing bio-based polyurethane according to claim 2, characterized in that: The castor oil is vacuum dried at 120° C. for 2 hours; the 1,4-butanediol is vacuum dried at 60° C. for 3 hours, and the solvent is N,N-dimethylformamide.
4. The method for preparing bio-based polyurethane according to claim 2, characterized in that: The reaction temperature was 60°C.
5. The use of bio-based polyurethane according to claim 1, characterized in that: Used to prepare zein / bio-based polyurethane nanofiber membranes.
6. The use of bio-based polyurethane according to claim 5, characterized in that: The method for preparing the zein / bio-based polyurethane nanofiber membrane comprises the following steps: S1: dissolving zein in a solvent to prepare a zein solution, adding the bio-based polyurethane solution to the zein solution, and stirring at room temperature for 12 hours to obtain a uniform bio-based polyurethane spinning solution; S2: The spinning solution is sucked up with a syringe and fixed on the propulsion pump, the needle is pulled and fixed on the reciprocating platform and connected to a DC high-voltage power supply, and the tin foil is wrapped on a metal roller receiving device as a collection device for the nanofiber membrane to obtain the corn protein / bio-based polyurethane nanofiber membrane.
7. The use of bio-based polyurethane according to claim 6, characterized in that: The mixing ratio of the corn protein solution to the bio-based polyurethane solution is 1.5-3.5:
4.
8. The use of bio-based polyurethane according to claim 7, characterized in that: The mixing ratio of the corn protein solution to the bio-based polyurethane solution is 3:
4.
9. The use of bio-based polyurethane according to claim 6, characterized in that: The solvent in step S1 is N,N-dimethylformamide.
10. The use of bio-based polyurethane according to any one of claims 6 to 9, characterized in that: In step S2, the propulsion flow rate of the propulsion pump is 0.5 mL / min, and the positive high voltage of the DC high voltage power supply is 0 to 30 kV.
Citation Information
Cited By
Nanofiber membrane as well as preparation method and application thereof
CN120537074A